Efficient biomass pretreatment using ionic liquids derived from lignin and hemicellulose - Socha, Aaron M. (National Academy of Sciences, 2014)
Ionic liquids (ILs), solvents composed entirely of paired ions, have been used in a variety of process chemistry and renewable energy applications. Imidazolium-based ILs effectively dissolve biomass and represent a remarkable platform for biomass pretreatment. Although efficient, imidazolium cations are expensive and thus limited in their large-scale industrial deployment. To replace imidazolium-based ILs with those derived from renewable sources, we synthesized a series of tertiary amine-based ILs from aromatic aldehydes derived from lignin and hemicellulose, the major by-products of lignocellulosic biofuel production. Compositional analysis of switchgrass pretreated with ILs derived from vanillin, p-anisaldehyde, and furfural confirmed their efficacy. Enzymatic hydrolysis of pretreated switchgrass allowed for direct comparison of sugar yields and lignin removal between biomass-derived ILs and 1-ethyl-3-methylimidazolium acetate. Although the rate of cellulose hydrolysis for switchgrass pretreated with biomass-derived ILs was slightly slower than that of 1-ethyl-3-methylimidazolium acetate, 90–95% glucose and 70–75% xylose yields were obtained for these samples after 72-h incubation. Molecular modeling was used to compare IL solvent parameters with experimentally obtained compositional analysis data. Effective pretreatment of lignocellulose was further investigated by powder X-ray diffraction and glycome profiling of switchgrass cell walls. These studies showed different cellulose structural changes and differences in hemicellulose epitopes between switchgrass pretreatments with the aforementioned ILs. Our concept of deriving ILs from lignocellulosic biomass shows significant potential for the realization of a “closed-loop” process for future lignocellulosic biorefineries and has far-reaching economic impacts for other IL-based process technology currently using ILs synthesized from petroleum sources.